Skill assessment in upper limb myoelectric prosthesis users: Validation of a clinically feasible method for characterising upper limb temporal and amplitude variability during the performance of functional tasks. (September 2017) - Thies, Sibylle B; Kenney, Laurence PJ; Sobuh, Mohammad; Galpin, Adam; Kyberd, Peter; Stine, Rebecca; Major, Matthew J
Highlights: We have identified a valid & low cost measure of prosthesis-user skill. Linear time normalization is a poor approach to compare functional task trajectories. Nonlinear dynamic time warping provides temporal and amplitude variability measures. Temporal variability measure differentiates amputees from controls. Temporal variability measure changes with practice. Abstract: Upper limb myoelectric prostheses remain challenging to use and are often abandoned. A proficient user must be able to plan/execute arm movements while activating the residual muscle(s), accounting for delays and unpredictability in prosthesis response. There is no validated, low cost measure of skill in performing such actions. Trial-trial variability of joint angle trajectories measured during functional task performance, linearly normalised by time, shows promise. However, linear normalisation of time introduces errors, and expensive camera systems are required for joint angle measurements. This study investigated whether trial-trial variability, assessed using dynamic time warping (DTW) of limb segment acceleration measured during functional task performance, is a valid measure of user skill. Temporal and amplitude variability of forearm accelerations were determined in (1) seven myoelectric prosthesis users and six anatomically-intact controls and (2) seven anatomically-intact subjects learning to use a prosthesis simulator over repeated sessions. (1): temporal variability showed clear group differences ( p <0.05). (2): temporal variability considerably increased on first use of a prosthesis simulator, then declined with training (both p <0.05). Amplitude variability showed less obvious differences. Analysing forearm accelerations using DTW appears to be a valid low-cost method for quantifying movement quality of upper limb prosthesis use during goal-oriented task performance.